2022
DOI: 10.4103/jomfp.jomfp_207_21
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dental anxiety with dental caries and periodontal disease among army recruits in Bangalore city - A cross sectional study

Abstract: Introduction: Dental anxiety can affect the dental health status of an individual leading to avoidance behavior, poor oral hygiene and periodontal health and delay in seeking necessary treatment. Objectives: This study aimed to assess the prevalence of dental anxiety in army recruits in Bangalore city and to explore the relationship of dental anxiety with dental caries and periodontal disease among army recruits in Bangalore city. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…The findings revealed a significant relationship between increased dental anxiety and a higher prevalence of dental caries among the participants. This aligns with previous research indicating that higher levels of dental anxiety are often observed in individuals with a history of dental caries [ 20 ]. The link between dental anxiety and dental caries can be explained through several mechanisms.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings revealed a significant relationship between increased dental anxiety and a higher prevalence of dental caries among the participants. This aligns with previous research indicating that higher levels of dental anxiety are often observed in individuals with a history of dental caries [ 20 ]. The link between dental anxiety and dental caries can be explained through several mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study the salivary cortisol levels was found to have a positive correlation with increased experience of dental caries (dmft/DMFT status) in children and the results were statistically significant ( Figure 1 ). The findings were similar to other studies which evaluated similar variables [ 14 , 17 , 18 , 19 , 20 ]. The increase in salivary cortisol levels with increased dental caries experience can be attributed to several factors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation